OPTIMIZATION OF THE COMPOSITION OF THE EXTRACTANT MIXTURE FOR THE EXTRACTION OF NATURAL ORGANIC COMPOUNDS FROM PROCESSING PRODUCTS OF VEGETABLE RAW MATERIALS AND THEIR FURTHER USE IN THE PRACTICE OF ANTI-CORROSION PROTECTION - Vorobyova, Viktoriia (Biota. Human. Technology, 2022)
Purpose. To theoretically substantiate and experimentally confirm the conceptual approach to the use of the i-PrOH-EtOH-H2O extractant system for obtaining plant extracts of grape, apricot, peach and tomato pomace with multifunctional anti-corrosion purposes. Methodology. The optimization of the three-component composition of the extractant system was carried out by the Scheffe simplex grid planning method with the construction of concentration triangles, the quantitative content of the sum of phenolic compounds, the total content of flavonoids, and the sum of volatile compounds was used as a response function, and the “composition-anticorrosion efficiency” dependence was established in neutral water and air environments. Scientific novelty. Use of the i-PrOH-EtOH-H2O extractant system in the ratio of propanol - 50 ÷ 40 %; ethanol – 25 ÷ 30 %; water – 15 ÷ 25 % with a polarity index 5.9 ÷ 6.3, is a criterion parameter for the extraction of substances that belong to different groups of natural organic compounds: plants secondary metabolism terpene and polyphenolic compounds. Conclusions. It was established that the optimal use of the i-PrOH-EtOH-H2O extractant system with a percentage ratio of solvents in the range of 50-40 %; 25 ÷ 30 %; 15 ÷ 25 %, respectively. The calculated polarity index is in the range of 5.87 ÷ 6.37 and is a criterion parameter for the system of extractants relative to the studied raw materials. By comparing the areas of optima with the construction of simplex lattice plans where the inhibitory effect is selected as the response function, it was established that the criterion parameters of the component composition of the extracts for their use as multifunctional inhibitors are the total content of phenolic compounds at the level of 90 ÷ ≥150 mg of the extract, flavonoids 22 ÷ ≥56 mg of extract and 70 ÷≥ 96 mg of terpene compounds per 100 g of extract.